Analisis Kandungan Boraks dan Formalin Pada Beberapa Pedagang Bakso di Kota Mataram - Adi Saputrayadi; Asmawati Asmawati; Marianah Marianah (IJECA (International Journal of Education and Curriculum Application), 2018)
This study aims to find out whether there are borax and formalin contents in meatballs sold by traders who have permanent meatball stalls in Mataram City. This is intended to have a better picture of the use of hazardous food additives by meatball traders in the city. The research sample was taken from several places of meatball traders in the city of Mataram. The sample consists of 12 meatball traders in Mataram city, representing six locations (sub-districts) in the city.  Sample members are meatball traders who have a permanent stall only, excluding street vendors and mobile traders. The study used an experimental method with laboratory testing. The procedure included the test of borax and formalin content and the analysis of organoleptic properties of meatballs. Based on the results of the analysis, of the 12 samples collected showed that none contained borax (0%), but 100% contained formaldehyde.